Approaches to Study Native Chromatin-Modifying Complex Activities and Functions - Galloy, Maxime; Lachance, Catherine; Cheng, Xue; Distéfano-Gagné, Félix; Côté, Jacques; Fradet-Turcotte, Amelie (Frontiers in Cell and Developmental Biology, 2021)
The modification of histones—the structural components of chromatin—is a central topic in research efforts to understand the mechanisms regulating genome expression and stability. These modifications frequently occur through associations with multisubunit complexes, which contain active enzymes and additional components that orient their specificity and read the histone modifications that comprise epigenetic signatures. To understand the functions of these modifications it is critical to study the enzymes and substrates involved in their native contexts. Here, we describe experimental approaches to purify native chromatin modifiers complexes from mammalian cells and to produce recombinant nucleosomes that are used as substrates to determine the activity of the complex. In addition, we present a novel approach, similar to the yeast anchor-away system, to study the functions of essential chromatin modifiers by quickly inducing their depletion from the nucleus. The step-by-step protocols included will help standardize these approaches in the research community, enabling convincing conclusions about the specificities and functions of these crucial regulators of the eukaryotic genome.